DESIGNING GAME APPLICATIONS OR EDUCATIVE TEACHING GAMES BASED ON INTERACTIVE MULTIMEDIA - Sari, Dita Novita; Nagara, Erliza Septia; Rahman, Khabibbur (Universitas Islam Negeri Raden Intan Lampung, 2024)
With the birth of technological developments, learning in schools or lectures inevitably applies computer-based learning systems, the presence of teaching process technology with the application of educational games for reciting the Koran can be an alternative learning when students are bored or feel tired during learning. Reciting the Koran refers to the activity of reading the Koran, which is a skill that every Muslim should have and needs to be instilled in children from an early age, starting before they enter school. This is an important part of forming their character. However, at an early age, children still tend to prefer playing, and limited methods of teaching the Koran may not be interesting enough for them. Therefore, an interactive learning method is needed using audiovisual aids, such as educational games. This approach not only makes learning more interesting, but also more interactive. This application can increase children's understanding and knowledge about the Islamic religion, especially in terms of reciting the Koran. By applying the concept of learning while playing, children become more comfortable, interested and happy in understanding and practicing the teachings of the Islamic religion.